Formulation and evaluation of propolis extracts based shampoo on dandruff causing bacteria - Wasu, Manjulah; Ramarau, Nitya Kumari; Muhammad Hafiz, Yahya; Syed, Mahmood; Nadiya, Abdul Halim; Rajaletchumy, Veloo Kutty (Malaysian Society for Microbiology, 2020)
Aim: Dandruff is characterized by the white flakes in the hairs and can be caused by dry skin and mainly by fungal growth of Malassezia yeasts. To treat this condition mainly synthetic type of active ingredient shampoos are used which gave severe adverse effect toward users like hair fall and weakening of the hair roots. In this study, we formulate a shampoo containing an active ingredient “Propolis” an antimicrobial agent which is also known as bee glue. Formed by the combination of bee wax and flower exudate collected from the flower bud. Methodology and results: In this study, propolis extracts have been used as the antimicrobial agent in the shampoo formulation for treating dandruff-causing bacteria, Staphylococcus aureus. Interestingly, the developed propolis shampoo showed is 10-fold more effective against S. aureus compared to the propolis extracts alone. This is due to the presence of Tween 80 as the surfactant used in the formulation which adds to this antibacterial effect. The formulated shampoo was also compared with the commercially available shampoo (Safi Shayla brand) for physicochemical properties. Overall evaluation of the shampoo with propolis found to have pH (6-7), good foaming ability, less wetting time, a good percentage of solid content and viscosity. Also, the formulated shampoo has greater stability under accelerated room temperature and accelerated the ageing condition. Conclusion, significance and impact of study: This study demonstrated the propolis extracted can be used as a potential antimicrobial agent. As it came from the natural resource the acceptance will high among the consumers.